Dampak Karakteristik Dewan Direksi terhadap Kinerja Keuangan pada Perusahaan Kriteria Syariah Sektor Perdagangan, Jasa, dan Investasi - Dadang Hermawan; Setiawan Setiawan; Putri Calvina Eka (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study is to analyze the impact of board of characteristics indicators on ROA, as well as educational and experiential moderation tests on these influences. Trade, service and investment sector companies registered with ISSI are used as a population. The secondary data used, namely ROA, size, gender, and independence of the board of directors, as well as education and experience as moderation variables, were obtained from the Annual Financial Statements for the period 2018-2020. The analysis methods used are model output, inner model and hypothesis testing with Warp Pls 7.0. The result of this study is that the size of the board of directors and independent directors affects the ROA but is not able to be moderated by education and experience. Female directors have no effect on ROA and are incapable of being moderated by experience but can be moderated by education.